Clarification requests as a method of pursuing understanding in CLIL physics lectures. Issue 3 (2nd September 2018) - Kääntä, Leila; Kasper, Gabriele
Abstract: Using multimodal conversation analysis, this article examines how students strive to resolve non-understandings through requests for clarification during teacher-fronted physics lectures taught in English in Finland. The findings provide new insights on the sequential environments in which students launch the requests (i.e. between or during teacher's explanation turns) and how different problem categories (e.g. language, conceptual, textual) are made relevant and oriented to in the requests. Moreover, the findings show the role of different textual objects (e.g. inscriptions on the board) in the formulation and resolution of the clarification requests as well as the relevance of students' note-taking to both their proximal and distal goals of trying to understand the instruction. Overall, the clarification requests are shown to influence in different ways the teacher's instructional process and offer valuable feedback to the teacher about the success of his explanations, i.e. how students understand them and whether he can proceed with his instructional agenda. Finally, the findings shed new light on how the integration of language and content is oriented to and accomplished by participants during teacher-fronted lectures in content-based lessons taught in a foreign language.